16 Bioresorbable vascular scaffolds implanted for acute coronary syndrome are associated with reduced early strut coverage. (24th April 2016) - Giblett, JP; Brown, AJ; Keevil, H; Hoole, SP; West, NEJ
Abstract : Background: Studies have suggested that neointimal growth and strut coverage is reduced in patients with acute coronary syndrome (ACS) receiving metallic stents. Use of more biocompatible devices such as bioresorbable vascular scaffolds (BVS) may facilitate early neointimal growth strut coverage. We aimed to assess whether neointimal growth is affected by clinical presentation, in a population undergoing BVS implantation. Methods: BVS were implanted in patients for stable angina (SA) or ACS using optical coherence tomography (OCT) guidance. Repeat OCT was performed at follow-up (median 74 days), and BVS analysed at 1mm intervals for measures of scaffold/flow area, apposition, neointimal growth and strut coverage. Results: 29 BVS were included (62% post ACS). There were no differences between procedural or lesion characteristics. Post-deployment, all BVS achieved >90% predicted scaffold area. Only 1.64% struts were incompletely apposed, compared to 0.47% at follow-up (p = 0.006). Reductions in mean scaffold (-4.0%, p = 0.01) and flow (-8.4%, p < 0.001) areas were observed at follow-up, with larger reductions in mean flow area for SA (-14.5 ± 14.2 vs. -4.9 ± 7.9%, p = 0.03). ACS led to reduced neointimal growth (0.51 ± 0.18 vs. 0.87 ± 0.37mm2, p = 0.002), and increased percentage of uncovered struts (2.68 ± 1.67 vs. 1.43 ± 0.87%, p = 0.015). Conclusions: Neointimal growth and strut coverage is reduced following ACS in patients receiving BVS at an early timepoint, consistent with studies in metallic stents. This suggests use of more biocompatible devices may not improve early strut coverage.